Comparison of Faradaic reactions in capacitive deionization (CDI) and membrane capacitive deionization (MCDI) water treatment processes. (1st September 2017) - Tang, Wangwang; He, Di; Zhang, Changyong; Kovalsky, Peter; Waite, T. David
Abstract: Capacitive deionization (CDI) and membrane capacitive deionization (MCDI) are the most common cell architectures in the use of CDI for water treatment. In this work, the Faradaic reactions occurring in batch-mode CDI and MCDI processes were compared by investigating the variation of H2 O2 and dissolved oxygen (DO) concentrations, pH, conductivity and current during charging and discharging under different charging voltages. During charging, the H2 O2 concentration in CDI increased rapidly and then decreased while almost no H2 O2 was generated in MCDI due to the inability of oxygen to penetrate the ion exchange membrane. Chemical kinetic models were developed to quantitatively describe the variation of H2 O2 concentration and found to present satisfactory descriptions of the experimental data. The pH drop during charging could be partially explained by Faradaic reactions with proton generation associated with oxidation of the carbon electrodes considered to be the major contributor. The electrode potentials required for the induction of Faradaic reactions were analyzed with this analysis providing robust thermodynamic explanations for the occurrence of carbon oxidation at the anode and H2 O2 generation at the cathode during the ion adsorption process. Finally, electrochemically-induced ageing of the carbon electrodes and the resulting performance stability were investigated. The findings in this study contribute to a better understanding of Faradaic reactions in CDI and MCDI and should be of value in optimizing CDI-based technologies for particular practical applications. Graphical abstract: Highlights: Faradaic reactions occurring in CDI and MCDI have been compared. Oxygen reduction at the cathode is inhibited by cation exchange membranes. Electrode potentials were analyzed to reveal the mechanism behind Faradaic reactions. H2 O2 concentration changes during charging and discharging satisfactory modeled. Original and ageing carbon electrodes were characterized.